2013
DOI: 10.1111/acer.12081
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Nonspecific Effects of Naltrexone on Goal-Directed and Habitual Models of Alcohol Seeking and Drinking

Abstract: Introduction The opioid receptor antagonist naltrexone (NTX) reduces goal-directed alcohol drinking in rats presumably by blunting alcohol reward. However, different operant conditioning behavior can be produced by different reinforcement schedules, with goal-directed operant behavior being more sensitive to changes in reward value than less flexible, habit-associated models. Objectives We tested the hypothesis that NTX more effectively reduces alcohol drinking and seeking in a goal-directed than in a habit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…Excitingly, recent work has shown that naltrexone has differential effects on alcohol seeking in animals that are trained on habit-promoting schedules. Specifically, it was observed that the ability of naltrexone to reduce cue-mediated ethanol seeking and ethanol consumption in rats was greater in rats that were trained on a ratio schedule, thought to maintain goal-directed behavior, as compared to rats trained on a habitpromoting interval schedule (Hay et al, 2013). …”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitingly, recent work has shown that naltrexone has differential effects on alcohol seeking in animals that are trained on habit-promoting schedules. Specifically, it was observed that the ability of naltrexone to reduce cue-mediated ethanol seeking and ethanol consumption in rats was greater in rats that were trained on a ratio schedule, thought to maintain goal-directed behavior, as compared to rats trained on a habitpromoting interval schedule (Hay et al, 2013). …”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…However, a few studies looking at drug and ethanol habits in animals exist (Belin & Everitt, 2008; Miles, Everitt, & Dickinson, 2003; Zapata, Minney, & Shippenberg, 2010). Several labs have published on habitual ethanol seeking using a lithium chloride devaluation paradigm (Barker et al, 2014; Barker, Torregrossa, Arnold, & Taylor, 2010; Dickinson, Wood, & Smith, 2002), specific satiety devaluation (Corbit et al, 2012; Hay, Jennings, Zitzman, Hodge, & Robinson, 2013) or contingency degradation (Barker et al, 2014) but to our knowledge, no outcome inflation data have been published related to alcohol seeking habits. Importantly, ethanolseeking habits differ from food seeking habits in that the transition from actions to habits occurs more readily (Corbit et al, 2012; Dickinson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nevin et al, 1983). Although interpreted differently, naltrexone produced similar results in a study by Hay, Jennings, Zitsman, Hodge, & Robinson (2013).…”
Section: Discussionmentioning
confidence: 61%
“…In another study, mice chronically exposed to ethanol vapor and then trained to operantly self-administer ethanol were insensitive to ethanol devaluation compared to mice without the previous exposure [150]. Other studies have reported habitual alcohol seeking, but either did not compare ethanol to sucrose self-administration [53] or did not detect differences [55, 56]; however, these studies did not include a prior ethanol exposure period, but only ethanol self-administered in the operant chamber. Taken together, these studies demonstrate that alcohol self-administration can transition from a goal-directed to a habitual behavior in rodents, and that a history of alcohol exposure can promote the speed of this transition.…”
Section: Alcohol Effects On Habitual Behaviormentioning
confidence: 99%